2020
DOI: 10.1186/s12889-020-08558-z
|View full text |Cite
|
Sign up to set email alerts
|

Drinking patterns and hydration biomarkers among young adults with different levels of habitual total drinking fluids intake in Baoding, Hebei Province, China: a cross-sectional study

Abstract: Background: The purposes were to investigate the drinking patterns and hydration biomarkers among young adults with different levels of habitual total drinking fluids intake. Methods: A cross-sectional study was conducted among 159 young adults aged 18-23 years in Baoding, China. Total drinking fluids and water from food were assessed by 7-day 24-h fluid intake questionnaire and duplicate portion method, respectively. The osmolality and electrolyte concentrations of the 24 h urine and fasting blood samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 52 publications
3
21
0
2
Order By: Relevance
“…Blood pressure (BP) was measured twice to the nearest 2 mmHg, with at least a 15 min rest period before measurement by a professional nurse using an electronic sphygmomanometer (HEM-7051, Omron, Jiangsu, China). Two measurements were taken after 2 min intervals [ 24 ]. (BMI: weight (kg)/height squared (m)).…”
Section: Methodsmentioning
confidence: 99%
“…Blood pressure (BP) was measured twice to the nearest 2 mmHg, with at least a 15 min rest period before measurement by a professional nurse using an electronic sphygmomanometer (HEM-7051, Omron, Jiangsu, China). Two measurements were taken after 2 min intervals [ 24 ]. (BMI: weight (kg)/height squared (m)).…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional study conducted among young adults revealed that participants with higher total drinking fluids had better hydration status, with lower urine osmolality and higher urine volume than those with lower total drinking fluids. However, no differences were found in plasma biomarkers [17]. Similarly, young females with fluid intake of <1.2 L/d produced a smaller amount of more concentrated urine than participants with 2-4 L/d fluids intake [18].…”
Section: Introductionmentioning
confidence: 74%
“…The urine osmolality was used to determine the hydration status for people in free-living conditions, as well as the urine color [13][14][15][16]. It was showed that the urinary biomarkers varied according to the fluids' intake, both in China and other countries [17,18]. Studies also demonstrated that the hydration biomarkers, including the urinary and the plasma biomarkers, were significant in terms of predicting health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Water is one of the main components of the human body, which is vital for the performance of physiological processes, thermoregulation, and transport of nutrients [1,6,7,8]. Water consumption is influenced by numerous factors, including temperature, humidity, as well as the level of physical activity and lifestyle [15,18,21,27]. The most vulnerable groups to dehydration are children and adolescents, who are prone to excessive water loss, especially during physical activity and may not be aware of the need to restore lost fluid [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…The endocrine system is involved in a number of water metabolism processes, optimizing the flow and excretion of fluid in the body. The pancreas, as an organ of the digestive and endocrine systems, undergoes pronounced structural changes under conditions of dehydration [4,5,7], as well as during the use of alcohol, opioids and smoking [15,18,20,21,27]. Therefore, an important issue today is the understanding of risk factors, physiological and pathogenetic links of pancreas diseases, systematization and expansion of data in the world literature on this issue [6,16,20,25].…”
Section: Introductionmentioning
confidence: 99%